2014
DOI: 10.4103/0377-4929.134711
|View full text |Cite
|
Sign up to set email alerts
|

Primary yolk sac tumor of the cerebellar vermis: A case report

Abstract: Extragonadal germ cell tumors are rare and comprise 2-5% of all germ cell tumors. Seminoma/dysgerminoma, teratoma, yolk sac tumor (YST) and mixed germ cell tumors are few of the extragonadal germ cell tumors arising within the brain. Of these, primary pure YSTs arising in the brain are extremely rare and arise in the pineal (62%) and suprasellar (31%) regions. Primary YST occurring in the cerebellum is exceedingly rare, associated with a very poor prognosis and has been reported in less than 10 cases in litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 20 , 21 This microscopic similarity is shared with other malignant pathologies such as anaplastic ependymoma, atypical teratoid/rhabdoid tumor, lymphoma, rhabdomyosarcoma, malignant meningioma, and other forms of highly proliferative malignant neuroectodermal tumors. 5 , 20 , 22 Given this broad differential diagnosis, the final diagnosis of pPNET requires an extensive workup, including immunohistochemistry analysis and cytogenetic examination. Immunohistochemistry analysis shows positive expression of CD99, FLI-1, NKX2.2, GFAP, and synaptophysin and negative EMA expression.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 This microscopic similarity is shared with other malignant pathologies such as anaplastic ependymoma, atypical teratoid/rhabdoid tumor, lymphoma, rhabdomyosarcoma, malignant meningioma, and other forms of highly proliferative malignant neuroectodermal tumors. 5 , 20 , 22 Given this broad differential diagnosis, the final diagnosis of pPNET requires an extensive workup, including immunohistochemistry analysis and cytogenetic examination. Immunohistochemistry analysis shows positive expression of CD99, FLI-1, NKX2.2, GFAP, and synaptophysin and negative EMA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Serum AFP level is a common indicator for evaluating the treatment response to YSTs. [7] Studies have shown that serum AFP >1000 ng/mL at the time of diagnosis is a risk factor for subsequent [10] M 23 Pineal region No Yes No NR 2017 [11] M 17 Hypothalamic and Pineal region Yes Yes Yes Alive 2014 [12] M 2 Cerebellar vermis Yes Yes No NR 2014 [13] F 45…”
Section: Discussionmentioning
confidence: 99%
“…Germinomas typically arise in regions adjacent to the third ventricle, such as the pineal body and neurohypophysis, but they may be present also in the basal ganglia. Germinomas originating in the cerebellum are quite rare [ 5 – 11 ] (see Additional file 2 : Table S1); in one study, only three of 153 intracranial GCTs were located in the cerebellum [ 12 ]. It is not difficult to diagnose intracranial GCTs when they have a typical location and radiographic features.…”
Section: Discussionmentioning
confidence: 99%